Weapon injuries in the crusader mass graves from a 13th century attack on the port city of Sidon (Lebanon) - Mikulski, Richard N. R.; Schutkowski, Holger; Smith, Martin J.; Doumet-Serhal, Claude; Mitchell, Piers D. (PLOS ONE, 2021)
Archaeological excavations close to St Louis’ castle in Sidon, Lebanon have revealed two mass grave deposits containing partially articulated and disarticulated human skeletal remains. A minimum of 25 male individuals have been recovered, with no females or young children. Radiocarbon dating of the human remains, a crusader coin, and the design of Frankish belt buckles strongly indicate they belong to a single event in the mid-13th century CE. The skeletal remains demonstrate a high prevalence of unhealed sharp force, penetrating force and blunt force trauma consistent with medieval weaponry. Higher numbers of wounds on the back of individuals than the front suggests some were attacked from behind, possibly as they fled. The concentration of blade wounds to the back of the neck of others would be compatible with execution by decapitation following their capture. Taphonomic changes indicate the skeletal remains were left exposed for some weeks prior to being collected together and re-deposited in the defensive ditch by a fortified gateway within the town wall. Charring on some bones provides evidence of burning of the bodies. The findings imply the systematic clearance of partially decomposed corpses following an attack on the city, where adult and teenage males died as a result of weapon related trauma. The skeletons date from the second half of the Crusader period, when Christian-held Sidon came under direct assault from both the Mamluk Sultanate (1253 CE) and the Ilkhanate Mongols (1260 CE). It is likely that those in the mass graves died during one of these assaults.